Noncommunicable diseases, access to essential medicines and universal health coverage - David Beran; Hanne Bak Pedersen; Jane Robertson (Taylor & Francis Group, 2019)
Universal Health Coverage is key to reach the overall health-related Sustainable Development Goal, and within this, access to safe, effective, quality, and affordable essential medicines is critical. Currently, medicines for noncommunicable diseases in many countries are not available when needed and if they are present, are unaffordable. Countries face the challenges of rising prevalence of noncommunicable diseases due to increasing risk factors and ageing populations, along with under-diagnosis and under-treatment. Providing noncommunicable disease medicines is only one piece of a complex picture of providing care within Universal Health Coverage that requires strengthening health-care systems, as well as financial resources, priority setting, and monitoring and evaluation systems. Financing for Universal Health Coverage needs to enable adequate resources to be allocated for medicines with a focus on equity as well as priority setting for noncommunicable diseases medicines for reimbursement in benefits packages, efficient procurement and distribution of these medicines, supported by price regulation. These processes need to be evidence-based, transparent and grounded on national values and priorities. Monitoring and evaluation of availability and affordability are key components of sustainable reimbursement systems. With the current Universal Health Coverage agenda, the World Health Organization and countries can no longer ignore the issue of access to medicines for noncommunicable disease and need to develop the appropriate responses in order to guarantee equitable access.